2018
DOI: 10.3390/tropicalmed3010016
|View full text |Cite
|
Sign up to set email alerts
|

Community Awareness on Rabies Prevention and Control in Bicol, Philippines: Pre- and Post-Project Implementation

Abstract: Rabies is endemic in the Philippines. To support the rabies campaign in the Bicol region at the southeastern part of Luzon, the BAI-OIE Stop Transboundary Animal Diseases and Zoonoses (STANDZ) Rabies project was implemented in the pilot provinces of Camarines Norte, Camarines Sur, Albay, and Masbate. A community awareness survey was conducted with the residents of these provinces to determine their knowledge, attitude, and practices (KAP) on rabies during the start and end of the project. Qualitative, descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Identifying and reducing direct contact between wild and domestic animals and humans including awareness campaigns to limit contacts with wildlife (e.g., reduce wildlife feeding) may prevent human rabies exposures ( 23 ). Patients presenting with animal-bite injuries provide a valuable source of surveillance data on rabies viruses transmitted by bites, including potential exposure risks and evidence of circulation among different reservoir hosts ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying and reducing direct contact between wild and domestic animals and humans including awareness campaigns to limit contacts with wildlife (e.g., reduce wildlife feeding) may prevent human rabies exposures ( 23 ). Patients presenting with animal-bite injuries provide a valuable source of surveillance data on rabies viruses transmitted by bites, including potential exposure risks and evidence of circulation among different reservoir hosts ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the current study showed an increase in the knowledge of Orang Asli on dog-led zoonotic infections following health education and promotion. Similarly an evaluation of rabies prevention and control project among dog owners in Philippines showed a significant increase in the knowledge of the community concerning rabies [33]. A classroombased lesson on rabies among primary school children in Malawi also showed an increased in the knowledge of the children on rabies and how to be safe around dogs [34].…”
Section: Knowledgementioning
confidence: 99%
“…The attitude to dog associated infections was good and improved post intervention but further improvement is dependent on the knowledge of the community because lack of basic knowledge in diseases transmission has direct influence on positive attitudes and practices [39]. In general, studies conducted in Philippines [33], China [23], Nigeria [40], Canada [39] and Australia [13] showed good attitudes towards dog associated infections. In Nigeria people felt that children should not play with unknown dogs and that they would wash wound after a dog bite with soap and water [35,40].…”
Section: Attitudementioning
confidence: 99%
“…23 Jan 2020). Acquired knowledge, when not emphasized or reiterated during class discussions (Barroga et al 2018), tends to diminish and this poses a challenge to younger students when it comes to applications of their learnings from IEC sessions. When students can recall information and then respond appropriately to circumstances (e.g.…”
Section: Introductionmentioning
confidence: 99%